(untitled) (Práxis Educativa, 2025)
This article aims to analyze the results of the self-assessment of the Graduate Program in Education at the University of Brasília (UnB) during the 2021–2024 four-year period, seeking to understand the meanings and scope of the actions carried out. The methodology involved documentary analysis related to the evaluation conducted by the Coordination for the Improvement of Higher Education Personnel (CAPES) and the program itself, meetings with research lines, and an in-person thematic workshop. The theoretical framework addressed evaluation (Cunha, 2005; Dias Sobrinho, 2018); graduate evaluation (CAPES, 2019a, 2019b, 2025; Verhine; Souza, 2021); and self-assessment (Belloni, 1996; Belloni; Belloni, 2003; Leite, 2005, 2006; Leite et al., 2020; Saul, 2002; Souza; Duarte; Seiffert, 2022). The results highlighted the need to: reduce the number of research lines from seven to five; improve the alignment of projects with these lines, the faculty size, and the academic production of both professors and students; review accreditation and reaccreditation criteria; and invest in strengthening the program’s educational identity, even though Education has a markedly interdisciplinary character. Keywords: Graduate in education. Self-assessment. Results.